Time-dependent prognostic value of coronary plaque burden and hyperemic myocardial blood flow - Jorge Dahdal; Teemu Maaniitty; Ruurt A. Jukema; Nick S. Nurmohamed; Pieter G. Raijmakers; Roel S. Driessen; Matias Mäenpää; Sarah Bär; R. Nils Planken; Niels van Royen; Jeroen J. Bax; Antti Saraste; et al. (European Journal of Nuclear Medicine and Molecular Imaging, 2026)
Abstract Rationale The time-dependent contributions of coronary atherosclerotic plaque burden and myocardial ischemia to clinical outcomes in suspected coronary artery disease (CAD) remain uncertain. This study aimed to evaluate the temporal associations of quantitatively assessed plaque burden and ischemia with cardiovascular events. Methods We studied 1,385 patients with suspected CAD who underwent coronary computed tomography angiography (CCTA) and [ 15 O]H₂O positron emission tomography (PET) perfusion imaging. Plaque burden was measured as percent atheroma volume (PAV) using AI-based CCTA analysis. Myocardial perfusion was evaluated by regional hyperemic myocardial blood flow (hMBF) using PET. Adjusted Cox regression models, including both PAV and hMBF, were used to assess associations with a composite outcome (death, non-fatal myocardial infarction, unstable angina) at 3, 6, and 9 years. Results The median follow-up time was 7.1 years, during which 185 patients (13.4%) experienced the outcome. Higher per-patient PAV (per 1%) was consistently and independently associated with increased event rate across all three timepoints (aHR 1.035–1.047, all p < 0.001). Lower regional hMBF (per 0.1 mL/min/g) was independently associated with events at 3 years (aHR 1.050, p = 0.004) and 6 years (aHR 1.028, p = 0.024), but not at 9 years (aHR 1.020, p = 0.063). After excluding early revascularization patients, regional hMBF remained associated with outcomes at all timepoints. Conclusions Plaque burden and regional hMBF are independent markers of cardiovascular risk. Plaque burden remained consistently associated with adverse clinical outcomes throughout follow-up, whereas regional hMBF was primarily related to short- and intermediate-term events, likely influenced by the effects of myocardial revascularization. Graphical abstract Cox models were developed incorporating both per-patient PAV and regional hMBF, with adjustment for clinical covariates and early revascularization status. AI = artificial intelligence; CCTA = coronary computed tomography angiography; PAV = percent atheroma volume; PET = positron emission tomography; hMBF = hyperemic myocardial blood flow; MI = myocardial infarction; UA = unstable angina.